Characterization and Economics of Farming Systems in Southern Rajasthan - Singh, Hari; Sharma, S K; Dashora, L N; Burak, S S; Meena, G L (Annals of Arid Zone, 2016)
A characterization survey of 144 farmers was conducted during 2010-11 in Chittorgarh and Rajsamand districts of southern Rajasthan. Crop-livestock and crop-livestock-horticulture farming systems were adopted by 66 and 34% of the farmers. Among different enterprises, crop production contributed 71 to 74% to total income of crop-livestock farming system and 23-29% in crop-horticulture-livestock farming system. The contribution of livestock in total income of farming system ranged from 23 to 29%. Horticulture contributed 11 to 35% to the total income of farming system. Large farmers received Rs. 49,852 and Rs. 37,385 ha-1 more net income than small and medium category of farmers, respectively, from crop-animal husbandry farming system and Rs. 87,710 and Rs. 51,161 ha-1 more from crop-animal husbandry-horticulture farming system, respectively. Study revealed that 91% of the farmers in Chittorgarh and Rajsamand districts face non-availability of quality seed as a major constraint. Lack of cross-bred and exotic breed animals resulted in low productivity of animals for 87.5% of the farmers. About 87.5% farmers suggested the need for making available good quality planting material for horticultural crops. Key words: Farming system, economics, constraints, characterization.